Hybrid treatment of massive pulmonary embolism by catheter-directed and surgical embolectomy - Pietrasik, Arkadiusz; Gąsecka, Aleksandra; Leśniewski, Mateusz; Zieliński, Dariusz; Darocha, Szymon; Kurzyna, Marcin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Pulmonary embolism (PE) is a life-threatening disease, responsible for up to 300 000 deaths annually in the US, ranking among the leading causes of cardiovascular mortality [1]. Systemic thrombolytic therapy is recommended for patients with high-risk PE [2]. Yet, thrombolysis is contraindicated or has failed in numerous patients. Surgical or percutaneous catheter-directed therapies are alternative treatment options. We present a case of massive pulmonary embolism in a patient with high-risk PE, visualized during pulmonary angiography and extracted en bloc by surgical embolectomy.